2002
DOI: 10.2527/2002.8071771x
|View full text |Cite
|
Sign up to set email alerts
|

Simulated preslaughter holding and isolation effects on stress responses and live weight shrinkage in meat goats1

Abstract: The objective of this experiment was to determine the effects of preslaughter isolation and feed withdrawal duration on physiological responses and shrinkage in goats. A total of 84 Spanish does (36 mo of age, average weight 35 kg) were individually weighed and scored for excitability before two replicate (day) trials. The does were feed-deprived (FD) or fed (F) in holding pens (treatment, TRT) for either 0, 7, 14, or 21 h (TIME). At the end of the holding periods, FD and F does were blood-sampled (n = 6 does/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 41 publications
7
80
1
5
Order By: Relevance
“…Knowles et al (1995) found that transportation and food deprivation in sheep for a period of 24 h resulted in increased concentrations of NEFAs. This result was similar to that found by Kannan et al (2002), who evaluated food restriction as a stressor.…”
Section: Plasma Metabolitessupporting
confidence: 81%
See 2 more Smart Citations
“…Knowles et al (1995) found that transportation and food deprivation in sheep for a period of 24 h resulted in increased concentrations of NEFAs. This result was similar to that found by Kannan et al (2002), who evaluated food restriction as a stressor.…”
Section: Plasma Metabolitessupporting
confidence: 81%
“…The blood was stored at 4 °C until centrifugation to obtain the plasma, and plasma was then aliquoted into Eppendorf tubes and frozen at -20 °C until it was thawed for further experimentation. Plasma glucose, lactate, cortisol, NEFAs and CK activity were analyzed according to the methods of Kannan et al (2000Kannan et al ( , 2002.…”
Section: Measurements and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifting animals from different sources in high stocking density with little or no space to establish social order aggravates the incidence of fighting and vocalization. This led to severe stress in the subordinate animals that continues to live under alarm, tension and anxiety (Kannan et al, 2002). When cows are added to a socially stable group, the entire group disrupted through threat, butting and physical aggression until the added cows have found their place in the social structure of that group (Grant and Albright, 2001).…”
Section: Social Effects Of Shifting Between Groupsmentioning
confidence: 99%
“…The law states that water must be 'available' to all animals at all times and feed if necessary when animals are lairaged for more than 12 h. Pre-slaughter feed deprivation helps reducing carcass contamination (Gregory & Grandin, 1998). However, prolonged feed deprivation may increase stress responses, metabolic changes and body weight loss (Kannan et al, 2002). Sheep lose 5-8% of their live weight during a 24 h journey without access to food (Knowless, 1998).…”
Section: Introductionmentioning
confidence: 99%